Lime and phosphogypsum impacts on soil organic matter pools in a tropical Oxisol under long-term no-till conditions - Carmeis Filho, Antonio C.A. [UNESP] (2017)
Improving soil organic matter (SOM) quality in tropical acid soils is important for increasing the sustainability of agricultural ecosystems. This research evaluated the effect of the surface application of lime and phosphogypsum on the quality and amount of SOM in a long-term crop rotation under no-till conditions. The research was performed in a kaolinitic, thermic Typic Haplorthox for 12 years with annual crops under no-till. The treatments included no soil amendments, and amendment with phosphogypsum, lime, and lime + phosphogypsum. After three applications of soil amendments (2002, 2004, and 2010), surface liming increased the SOM input through addition of aboveground and root biomass, varying amount according to crop species, growing season, and soil depth. Although phosphogypsum had no effect on plant biomass production, the application of phosphogypsum with lime increased nitrogen (N) by up to 50% in the uppermost soil depths. The application of lime alone significantly increased the total organic carbon (TOC) at all depths, although the greatest effects were observed at 0.10–0.20 and 0.20–0.40 m, with an increase of 44% and 41%, respectively. Moreover, lime + phosphogypsum also exhibited the highest potential for C mineralization, which was attributed to an increased proportion of TOC as particulate organic carbon (POC). The proportion of TOC as humin and fulvic acid increased with the application of lime + phosphogypsum at 0–0.05 m, with an increase from 55% to 92% and from 1.4% to 1.6%, respectively. Overall, the combination of lime and phosphogypsum increased both the labile and stable C pools.